Structural organization of the olfactory epithelium of a spotted snakehead fish, Channa punctatus - D.K. Mandal; D. Roy; L. Ghosh (Acta Ichthyologica et Piscatoria, 2005)
Background. Enormous diversities exist regarding shape, number, and arrangement of the olfactory lamellae, distribution of the sensory and non-sensory epithelium as well as the abundance of various receptor cells among different teleosts. This study was aimed at describing the morphology, histology and SEM ultrastructure of the olfactory epithelium of a spotted snakehead fish, Channa punctatus (Bloch, 1793). Materials and methods. OE of C. punctatus was examined through LM and SEM. Results. Olfactory epithelium of C. punctatus containing 18 to 20 lamellae provides a large surface area. Sensory epithelium possesses both ciliated and microvillous olfactory receptor cells (ORC), which are intermingled and distributed throughout the epithelium. ORCs are arranged in alternate rows with supporting cells (SCs). ORC is columnar cell with a round cell body, an axonal process and a long dendrite. The apical surfaces of the ORCs are provided either with 10–12 cilia or numerous microvilli and the SCs with fingerprint like microridges. ORCs with rod-shaped dendrite ending were found in small numbers. Non-sensory epithelium is composed of ciliated nonsensory cells (cNSC) and covered with a dense carpet of cilia, which help in ventilating the olfactory chambers. Conclusion. A large surface area of OE, the high density of both ciliated and microvillous ORC and adequate arrangement for ventilating the olfactory chambers indicate that C. punctatus is very much dependent on its olfactory sense.